Contribuição indígena à hidronímia maranhense - Edson Lemos Pereira (2022)
With the arrival of the French in Maranhão in 1612, Tupi language and culture peoples were the people that most had contact with Europeans. After this, with the expulsion of the French by the Portuguese, this contact was even greate, the Portuguese taught the religion and the western world way of working, and with their help they penetrated the interior of the continent throught the great rivers as Munim, Mearim, Pindaré, Itapecuru, facilitators of demographic movements and trade from the metropolis to the interior. Considering this reality and the importance of hydrography for the development of the State, we selected as object of study, the maranhense hydronymy of indigenous origin, understanding hydronymy as part of Onomastics that deals with studying the baptismal names of water elements in general, no matter its linguistic nature. In such case, we aim to investigate the proper names of indigenous origin that give name the maranhense hydronymy. For data collection, we conducted research in the Agência Nacional das Águas – ANA, in the Instituto Brasileiro de Geografia e Estatística – IBGE for collecting current maps and in the public collection of the state of Maranhão for the collection of old maps. To obtain the corpus, we carried out a survey of: (i) all hydronymy of the North Maranhense Mesoregion, through current IBGE maps and (ii) of hydronymy in maps of the Maranhão territory of the 17th, 18th, 19th and 20th centuries, in the works of chroniclers such as Claude d’Abbeville, Yves d’Évreux, Frei Francisco de Nossa Senhora dos Prazeres Maranhão and D. Frei Cristóvão de Lisboa. The studies of Dauzat (1922, 1938, 1946), Vasconcelos (1931), Dick (1990, 1992, 1999, 2000, 2001, 2004, 2007), Isquerdo (2006, 2009, 2010, 2011), Seabra (2006, 2008, 2010, 2012), Tapero (1995) Rosselló i Verger (2010) and Mujika Ulazia (2010) provided the basis for this research. The research corpus corresponds to the total of 518 indigenous hydronyms that generated the elaboration of 178 lexicographical-toponymic cards. The data showed (i) phytotopyms, such as Buriti, Bacuri, Cajá, Caju; (ii) zootopony, such as Curimatá, Papagaio, Sucuriú, Urubu; and (iii) hydrotyponym, such as Igarapé, Ipueira, Peritoró, Tibiri, as the most recurrent taxonomies. The variation in the scope of phonetics is more present, as in Pacoury > Bacuri; Acaiou > Caju; Yarammacarou > Mandacaru; Courimata > Curimatá; Courourou > Cururu; Iacou > Jacu, marked the Onomastic route. The toponymic phrase with the presence of the preposition de has, in almost all the phrases in which it is inserted, the semantic role of both denomination and presence or existentiality, as in Riacho da Curica, Vão do Jatobá. In this way, the linguistic aspects of the entities' baptismal name establish relationships between the culture and history of peoples and their place.